5(t+2)=2(t+3)

Simple and best practice solution for 5(t+2)=2(t+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(t+2)=2(t+3) equation:


Simplifying
5(t + 2) = 2(t + 3)

Reorder the terms:
5(2 + t) = 2(t + 3)
(2 * 5 + t * 5) = 2(t + 3)
(10 + 5t) = 2(t + 3)

Reorder the terms:
10 + 5t = 2(3 + t)
10 + 5t = (3 * 2 + t * 2)
10 + 5t = (6 + 2t)

Solving
10 + 5t = 6 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
10 + 5t + -2t = 6 + 2t + -2t

Combine like terms: 5t + -2t = 3t
10 + 3t = 6 + 2t + -2t

Combine like terms: 2t + -2t = 0
10 + 3t = 6 + 0
10 + 3t = 6

Add '-10' to each side of the equation.
10 + -10 + 3t = 6 + -10

Combine like terms: 10 + -10 = 0
0 + 3t = 6 + -10
3t = 6 + -10

Combine like terms: 6 + -10 = -4
3t = -4

Divide each side by '3'.
t = -1.333333333

Simplifying
t = -1.333333333

See similar equations:

| (2x-7)(x+3)(x-2)=0 | | (4x)+(3x-8)=90 | | x+x-20=54 | | 2x^2+2y^2+8x-12y+3=0 | | 8y+3=7y-7 | | 20-5/2 | | j^2+24j+23=0 | | 2(x-3)-4x=8-3(2x-1)+11 | | 2x+16=3x-25 | | 3x-25=2(y+8) | | 64=4+6(x+4) | | g^2-13g+22=0 | | j^2+6j=0 | | d^2-50d=0 | | 17y*3= | | (-9/7)x1/2/11x(-1/6) | | 5x+58=x+26 | | (a-2)*(a-2)= | | (6ln(7))-(6ln(1))= | | 9(d-4)-6=8(d-8)+46 | | 6x+30=2x+6 | | (h+7)(h-2)h=72 | | 4(2x-1)-2(x+3)=5 | | 5(r+5)=2(r-4)+1 | | 4U^3=64u | | x(670-x)=.35 | | (670-x)/x=.35 | | =x^2+mx-2x | | 5x+12=4x+2 | | -3(4y-6)+6y=4(y+4) | | 15b^2-24b-63=0 | | .35x-x^2=670 |

Equations solver categories